1999
DOI: 10.1016/s0005-2736(98)00199-0
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of polymeric and liposomal gene delivery systems with extracellular glycosaminoglycans: physicochemical and transfection studies

Abstract: Complexes of DNA with cationic lipids and cationic polymers are frequently used for gene transfer. Extracellular interactions of the complexes with anionic glycosaminoglycans (GAGs) may interfere with gene transfer. Interactions of GAGs with the carrier-DNA complexes were studied using tests for DNA relaxation (ethidium bromide intercalation), DNA release (electrophoresis), and transfection (pCMVbetaGal transfer into RAA smooth muscle cells). Several cationic lipid formulations (DOTAP, DOTAP/Chol, DOTAP/DOPE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
268
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(276 citation statements)
references
References 25 publications
8
268
0
Order By: Relevance
“…The excess positive charge of lipoplexes and polyplexes, which is required for full DNA compaction and nuclease resistance, implies strong interactions with solutes (eg blood proteins, 10 erythrocytes 2 ) and the extracellular matrix 11,12 under in vivo conditions. The mostly undesired consequences can be unintentional vector targeting, assembled vectors or their cationic component in order to confer the desired stability.…”
Section: Discussionmentioning
confidence: 99%
“…The excess positive charge of lipoplexes and polyplexes, which is required for full DNA compaction and nuclease resistance, implies strong interactions with solutes (eg blood proteins, 10 erythrocytes 2 ) and the extracellular matrix 11,12 under in vivo conditions. The mostly undesired consequences can be unintentional vector targeting, assembled vectors or their cationic component in order to confer the desired stability.…”
Section: Discussionmentioning
confidence: 99%
“…After intravenous injection of lipoplex, plasmid DNA would be dissociated from the cationic liposomes in the blood circulation by the interaction with biological components, such as blood constituents and proteoglycans. 25,27,28 Free DNA dissociated from cationic liposomes is susceptible to degradation by nucleases in the blood and the degradation products are excreted into the urine via the kidney and distributed throughout the body. Kawabata et al 29 have demonstrated these processes after i.v.…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 99%
“…[1][2][3][4] Of these, a significant portion have relied upon the use of polyethylenimine (PEI) as a carrier base due to its established efficiency as a gene compaction and delivery reagent. 2,[5][6][7][8][9] PEI has the highest cationic charge density of any macromolecule and is thus conducive to DNA condensation.…”
Section: Introductionmentioning
confidence: 99%